2021
DOI: 10.1038/s41598-021-85169-7
|View full text |Cite
|
Sign up to set email alerts
|

KLK3 SNP–SNP interactions for prediction of prostate cancer aggressiveness

Abstract: Risk classification for prostate cancer (PCa) aggressiveness and underlying mechanisms remain inadequate. Interactions between single nucleotide polymorphisms (SNPs) may provide a solution to fill these gaps. To identify SNP–SNP interactions in the four pathways (the angiogenesis-, mitochondria-, miRNA-, and androgen metabolism-related pathways) associated with PCa aggressiveness, we tested 8587 SNPs for 20,729 cases from the PCa consortium. We identified 3 KLK3 SNPs, and 1083 (P < 3.5 × 10–9) and 3145 (P &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…This suggests that prior studies of aggressive CaP did not fail to detect associations because of the nature of their sampling design. Additionally, we note that rs62113212, an intronic variant in KLK3 that has previously been associated with aggressive CaP, 57 is near monomorphic in Africa - which explains why it did not come up in our GWAS of different grade groups.…”
Section: Discussionmentioning
confidence: 89%
“…This suggests that prior studies of aggressive CaP did not fail to detect associations because of the nature of their sampling design. Additionally, we note that rs62113212, an intronic variant in KLK3 that has previously been associated with aggressive CaP, 57 is near monomorphic in Africa - which explains why it did not come up in our GWAS of different grade groups.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have suggested that the key to using kallikreins as biomarkers is to test them in combination; in fact, for colorectal, ovarian, and non-small cell lung cancer, kallikreins are more effective as multiparameter panels of biomarkers than as individual antigens. More detailed information on the transcriptional regulation of kallikreins would explain why they are dysregulated in particular diseases (prostate cancer) and, therefore, could represent biological variations as biomarkers [56][57][58][59][60]. Therefore, the observed changes of KLK3 in the participants of the two areas examined could represent a very first indication of an expanding study on the role of biomarkers as a promising way to assess the early effects of pollutants on female reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of interactions between KLK3 single nucleotide polymorphisms (SNPs) and other SNPs to identify interactions associated with prostate cancer aggressiveness support the notion that KLK3 and VEGF-C concertedly are involved in the regulation of prostate cancer tumor angiogenesis. Although not common, the VEGFC/KLK3 SNP-SNP interaction pair rs174776/rs3775202 was highly significantly associated with prostate cancer aggressiveness [76]. Since both SNPs are intronic and not predicted to change mRNA splicing, their effect is likely regulatory.…”
Section: Activation Of the Vegf-c And Vegf-dmentioning
confidence: 96%